Determinan Return Saham dengan Kualitas Pengungkapan Laporan Keuangan sebagai Variabel Moderasi - Fauzi, Muhammad Irfan; Hasan Mukhibad (Journal of Accounting, Economics, and Business Education, 2024)
Stock are an active and highly liquid invesment instrument. The movement of stock prices are volatile. Fundamental analysis can be a solution to deal with the risks. The purpose of this study is to examine the determine factor of stock return with financial report disclosure quality as a moderating variable. This research is a quantitive study using secondary data collected from historical stock data and financial report of companies incorporated into index 80 listed on the Indonesia Stock Exchange during 2019-2023. 66 companies were selected as sample with 330 unit of analysis. This study shows that earning per share and price earning ratio are able to effect stock returns significantly positive, while market capitalization and trading volume not able to affect stock return. Financial report disclosure quality was not able to moderate the relationship between earning per share, market capitalization, price earning ratio, and trading volume on stock returns. The results of this study are useful for investors to understand the role of financial indicators in describing company’s fundamental. Researcher found limitations where the variables used in this study were only able to explain the stock return variable by 1%. Therefore, further research with variations research model is expected.